Dieting reduces plasma tryptophan and alters brain 5-HT function in women. - Anderson, I; Parry-Billings, M; Newsholme, E; Fairburn, C; Cowen, P (1990)
A three week low calorie diet significantly reduced both total plasma tryptophan and the ratio of tryptophan to competing amino acids in a group of 15 healthy volunteers. Despite a similar percentage weight loss the reduction in plasma tryptophan was greater in women than men. In addition, only in women was dieting associated with increased prolactin secretion following intravenous tryptophan, a measure of brain 5-hydroxytryptamine (5-HT) function. These results suggest that dieting reduces the availability of circulating tryptophan for brain 5-HT synthesis. Women appear more vulnerable than men both to this effect and to its consequences for brain 5-HT function. Altered brain 5-HT function may play a part in some of the psychological consequences of dieting, including the development of clinical eating disorders.